UMPSA offers opportunity to continue studying through APEL - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 16 April 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) offers the opportunity to continue studies for adults and those who have previous experience including work experience to obtain academic qualifications.